Physical properties of cathode ray tube (CRT) used as aggregate for road pavement application - Ahmad Yusri Mohamad; Nur Izzi Md. Yusoff; Mohd Raihan Taha; Maslina Jamil (Penerbit Universiti Kebangsaan Malaysia, 2020)
The amount of electronic waste (e-waste) generated globally has been increasing steadily, including in Malaysia. Utilizing the e-waste as alternative recycled materials can help to conserve natural resources as well as reduce the demand for natural resources. Furthermore, recycled materials can be used in countries with limited aggregate resources. The present study aims to compare the physical properties CRT glass e-waste used as partial replacement for natural aggregates in road pavements. The study method for laboratory work were carried out in accordance with the American Society for Testing and Materials (ASTM) specifications. Three physical tests were carried out to determine the strength of the sample, i.e. Los Angeles abrasion test, specific gravity test and water absorption test. Result shows that CRT glass has a high value of 59.50% for the Los Angeles abrasion test, which exceed the specified requirement of 50%. The value for water absorption test shows that the CRT glass sample was able to achieve the specified requirement. The result for specific gravity test shows that the natural aggregates have a value higher than that of the CRT glass sample. Aggregates with higher specific gravity are generally stronger than those with lower specific gravity. Studies have to be carried out to identify the feasibility of using CRT e-waste glass as an alternative recycled material in the construction of road pavements.